Structures and crystal chemistry of the double perovskites Ba2LnB′O6 (Ln=lanthanide B′=Nb5+ and Ta5+): Part I. Investigation of Ba2LnTaO6 using synchrotron X-ray and neutron powder diffraction - Saines, P; Spencer, JR; Kennedy, B; Avdeev, M (2007)
The structure of 14 compounds in the series Ba2LnTaO6 have been examined using synchrotron X-ray diffraction and found to undergo a sequence of phase transitions from I2/m monoclinic to I4/m tetragonal to Fm over(3, -) m cubic symmetry with decreasing ionic radii of the lanthanides. Ba2LaTaO6 is an exception to this with variable temperature neutron diffraction being used to establish that the full series of phases adopted over the range of 15-500 K is P21/n monoclinic to I2/m monoclinic to R over(3, -) rhombohedral. The chemical environments of these compounds have also been investigated and the overbonding to the lanthanide cations is due to the unusually large size for the B-site in these perovskites. © 2007 Elsevier Inc. All rights reserved.